Islamic guidelines for healthful living - Rahman, Mohammad Tariqur; Abdul Karim, Jesmin Banu (Islamic Medical Association of North America, 2007)
This paper highlights the scientific advancements in immunology and other fields that have given deeper insights into healthful living by advocating guidelines similar to the ones revealed to mankind in the 7th century of the common era (CE) in the Qur'an and Hadith. Discussions are made linking published scientific evidence and recent discoveries in the field of immunology and related sciences with the related Islamic guidelines on various aspects of life. Scientific evidence is consistent with the benefits of the guidelines in Islam for cleanliness (e.g. bathing, ablution, miswāk), eating and drinking habits (e.g. giving importance for honey and olive oil, abstinence from alcohol, avoidance of excessive eating), lifestyle (e.g. managing stress, sex habits), breast feeding, and excretion of body waste in public places.